Have you seen this fish? Important contribution of stakeholder observations in documenting the distribution and spread of an alien fish species in Iceland - Theresa Henke; Hlynur Bárðarson; Magnús Thorlacius; Guðbjörg Asta Ólafsdóttir (NeoBiota)
To address the increasing global issue of biological invasions adequate long-term monitoring data is crucial. Due to substantial resource requirements such continuous monitoring remains largely underdeveloped across many countries. In recent years, experiential knowledge of the public, or specific stakeholder groups, has become increasingly popular to gather species’ occurrence data. In the context of aquatic alien species recreational fishermen often represent a valuable stakeholder group. Using the case study of alien European flounder (Platichthys flesus, Linneaus, 1758) in Iceland, we explore the benefits of incorporating stakeholder observation-based information with traditionally obtained data on the occurrence and distribution of an alien fish. We compiled records of European flounder reported by the recreational fishing community both when directly approached with an anonymous online survey as well as via social media conversations applying the approach of iEcology. We then contrasted this data with a compilation of European flounder records from databases at the Icelandic Marine and Freshwater Research Institute (MFRI). Our results show that including stakeholder-observation based distribution data in the monitoring of alien species offers significant advantage. While all data sources indicated similar patterns in the spread and distribution of European flounder in Iceland, they differed in the number of unique sites provided as well as their geographic distribution. Combining sources therefore allows to counteract inherent biases present across diverse sources. Our study furthermore indicates that interest in voluntarily reporting European flounder sightings decreased over time, but reemerged when stakeholders and/or the public were presented with an easily accessible opportunity to share information in the form of an online survey. We recommend implementing a monitoring approach for alien species that incorporates diverse sources of information and provides clear venues to report information for the public, and where possible involve stakeholders throughout the entire research process to holistically address biological invasions.